Análise dos aglomerados de risco espaço-temporais para leishmaniose visceral nos municípios de fronteira do Brasil, entre 2013 e 2022 - Moreira, William da Costa (2025)
Introduction: Visceral Leishmaniasis is an infectious disease that remains a significant public health challenge in Brazil, especially in border areas. Objective: to analyze the spatiotemporal risk distribution of Visceral Leishmaniasis in Brazil's border municipalities from 2013 to 2022. Method: an ecological study was conducted using confirmed cases of Visceral Leishmaniasis from the Notification of Diseases Information System. Crude incidence rates were calculated per 100,000 inhabitants. Spatial relative risk was determined using Kulldorff's technique, while temporal analysis used Joinpoint regression. Results: a total of 31,453 cases of Visceral Leishmaniasis were recorded in Brazil from 2013 to 2022, with an average annual incidence rate of 1.52/100,000. Federal units (1.02/100,000) and border municipalities (0.58/100,000) had lower incidence rates. The highest number of cases was among children and adolescents (51.78%) and males (62.92%), particularly in the Central Arc (58.49%), which showed a high relative spatial risk (71.49%). Three municipalities in the Northern Arc of Brazil in Roraima were identified with a high incidence rate (470.1/100,000) and a relative risk of 107.64 (p < 0.001). Fourteen municipalities, including Campo Grande, had an incidence rate of 76.3 per 100,000 inhabitants and a relative risk of 23.62 (p < 0.001). In high-risk municipalities, there was a 31.43% annual increase from 2020 to 2022, contrasting with the reduction observed from 2013 to 2020. In the Central Arc, there was an annual decrease of -12.07% from 2013 to 2020, followed by a 61.06% annual increase from 2020 to 2022 (p<0.05). Conclusion: Visceral Leishmaniasis continues to manifest territorially in Brazil, including in border municipalities, showing spatiotemporal risk clusters. Areas identified as high-risk should be prioritized in disease control actions.